Reading note 2: Internal governance of living landscapes - Navarrete Cruz, Angela; Piraux, Marc; Bergamini, Nadia; Triomphe, Bernard (2024)
This Note is the second of a series of reading notes reviewing selected literature on concepts, approaches, methods, and experiences that the Agroecology Initiative (AE-I) and particularly its WP1 employs for the emergence and consolidation of Agroecological Living Landscapes or Living Labs (ALLs) aimed at fostering Agroecological transitions. This note focuses on the Internal Governance of ALLs as a key aspect of how stakeholders interact in LLs and make decisions.